2020
DOI: 10.3390/plants9070830
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil Fertilization on Terpenoids and Other Carbon-Based Secondary Metabolites in Rosmarinus officinalis Plants: A Comparative Study

Abstract: Rosmarinus officinalis is an evergreen aromatic plant with important commercial interest as it contains numerous essential oils (composed of terpenoid compounds) and phenolic constituents (natural antioxidant compounds). This work aims at evaluating the concomitant effects of different inorganic and organic fertilization treatments and the subsequent increases in soil nutrient availability on terpenoids and other carbon-based secondary metabolites, e.g., flavonoids and phenolic compounds, in Rosmarinus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 89 publications
0
18
0
1
Order By: Relevance
“…Induction and parallel repression of specific secondary metabolite biosynthesis pathways were described before in Arabidopsis thaliana (Scheible et al, 2004). In addition, the contrary behaviour of flavonoid and terpenoid biosynthesis depending on nitrogen availability was shown before for Rosmarinus officinalis (Bustamante et al, 2020).…”
Section: Discussionmentioning
confidence: 60%
“…Induction and parallel repression of specific secondary metabolite biosynthesis pathways were described before in Arabidopsis thaliana (Scheible et al, 2004). In addition, the contrary behaviour of flavonoid and terpenoid biosynthesis depending on nitrogen availability was shown before for Rosmarinus officinalis (Bustamante et al, 2020).…”
Section: Discussionmentioning
confidence: 60%
“…In addition, the contrary behaviour of flavonoid and terpenoid biosynthesis depending on nitrogen availability was shown before for Rosmarinus officinalis (Bustamante et al. 2020 ).…”
Section: Discussionmentioning
confidence: 75%
“…Thus, the lack of variation in the flavonoid content in response to fertilization with cattle and poultry manures observed in this study can be partly explained by the lack of variation in Ca and P levels in the soil (Table 1) and in the Ca, P, and Mg levels in leaf tissue (Table 3). Besides, a high N availability is related to small contents of phenolic and flavonoid in some plants because of a competition between vegetative growth and phenolic synthesis via shikimic acid pathway (Bustamante et al 2020;Bénard et al 2011); this correlation was not found in P. incarnata (Reimberg 2006). This statement was reinforced in our study, where there was no variation in N content in leaves (Table 3) and no variation in flavonoid content (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Growers also suggest that fertilization with animal manure every 50 or 60 days after planting, in the range of 3 to 5 L m −2 , promotes a higher plant mass, larger leaves, and taller plants. However, for some plants, high N leaf concentrations have a negative correlation with total phenolic and total flavonoid contents in leaves (Bustamante et al 2020;Bénard et al 2011). Therefore, it is necessary to study the adequate supply of NPK in medicinal plants to attend the requirements for growth and phenolic synthesis.…”
Section: Introductionmentioning
confidence: 99%